Structural Improvements for Tall Buildings under Wind Loads: Comparative Study - Nicola Longarini; Luigi Cabras; Marco Zucca; Suvash Chapain; Aly Mousaad Aly (Shock and Vibration)
The behavior of a very slender building is investigated under wind loads, to satisfy both strength and serviceability (comfort) design criteria. To evaluate the wind effects, wind tunnel testing and structural analysis were conducted, by two different procedures: (i) Pressure Integration Method (PIM), with finite element modeling, and (ii) High Frequency Force Balance (HFFB) technique. The results from both approaches are compared with those obtained from Eurocode 1 and the Italian design codes, emphasizing the need to further deepen the understanding of problems related to wind actions on such type of structure with high geometrical slenderness. In order to reduce wind induced effects, structural and damping solutions are proposed and discussed in a comparative study. These solutions include (1) height reduction, (2) steel belts, (3) tuned mass damper, (4) viscous dampers, and (5) orientation change. Each solution is studied in detail, along with its advantages and limitations, and the reductions in the design loads and structural displacements and acceleration are quantified. The study shows the potential of damping enhancement in the building to mitigate vibrations and reduce design loads and hence provide an optimal balance among resilience, serviceability, and sustainability requirements.